Mythological roots of the city image in the works of neoclassicists (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article is devoted by investigation in development of an artistic image of city in the works of neoclassic poets. Aesthetic composed an image of city as subject of transient are defined. Specificity of aesthetic perception of city during different epoch and relationships of an aesthetic and art in image structure is analyzed. Ancient and Christian traditions helped to represent the image of city as the worldview. It allowed renovating its psychological and intuitive sense of existentialism of the author in controversial reality 20-30th of the XXth century.
Keywords: neoklassyky; neoklassytsyzm; city; myth; antiquity